Innovative interactive technologies in the training of professional education specialists by means of digital technologies - Hevko, Ihor; Siaonan, Se; Hongwei, Wu (Journal of Education, Health and Sport, 2023)
This article is devoted to the study and analysis of the role and influence of innovative interactive technologies in the training of professional education specialists using digital technologies. Digital technologies are becoming an increasingly integral part of our daily lives and impacting various fields, including education. The article examines the modern foreign and domestic experience of using modern innovative interactive technologies in the professional training of future vocational education specialists. The possibilities of implementing augmented reality (AR) and virtual reality (VR) to create immersive learning environments are described. Emphasis is placed on adaptive educational platforms that are able to individualize the educational process taking into account the personal needs and individual characteristics of students. The analysis of the influence of interactive technologies on the activity and interest of students, increasing the level of involvement and motivation to study was carried out. The advantages of these technologies in the training of specialists are analyzed, their impact on student motivation, understanding of complex concepts and the creation of interactive learning environments is noted. It highlights how the adaptability of learning platforms helps create personalized learning paths for each student, taking into account their needs and pace of learning. The experience of using innovative and interactive technologies in various fields, including education, science and technological development, is outlined. The results of the study indicate the importance of integrating digital technologies into the educational process to achieve more effective learning and development of relevant skills among students of vocational education.